2021
DOI: 10.4103/lungindia.lungindia_118_19
|View full text |Cite
|
Sign up to set email alerts
|

Ambispective study of adverse drug reactions in multi-drug resistant tuberculosis patients in Warangal, Telangana

Abstract: Background: Multidrug-resistant tuberculosis (MDR-TB) has become a global threat concerning to a risk of high mortality with the potential to cause adverse drug reactions (ADRs) which if not managed properly may affect patient compliance, resulting in below par treatment outcome. Aim: The aim of the study was to study, assess, and report the ADRs of patients diagnosed with MDR-TB. Subjects and Methods: An ambispective, observational study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…In the present study, the majority of ADRs were found mild (41.30%) and moderate (40.22%) followed by severe (18.48%). These results were dissimilar to those obtained in the study conducted by Fatima et al [16].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, the majority of ADRs were found mild (41.30%) and moderate (40.22%) followed by severe (18.48%). These results were dissimilar to those obtained in the study conducted by Fatima et al [16].…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, male (67.65%) patients were more affected due to adverse drug reactions as compared to females (32.35%) which were similar to the study conducted by Rathod et al [14] and Fatima et al [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations